Impact of the "A study on how a competitive customer management system creates an impact on increasing the brand image for online food delivery business" - Rahman, Md. Maksudur (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.